Studies on Atmospheric Pollution over Chennai - A Mega South East Coastal City in India (International Journal of Scientific Research and Management (IJSRM), 2017)
Pollutants are substances which, when present at high enough concentrations, produce harmfuleffects on people and/or the environment. Air pollution was first perceived as a local problem in urbanindustrialized areas, hence taller smoke-stacks for industries and power plants were a ready solution. Urbanpopulation is growing very rapidly throughout the world, besides the world population is urbanizing muchfaster than is growing. Air pollutants emitted from different sources are transported, dispersed or deposited by meteorological and topographical conditions.